2018
DOI: 10.1038/s41558-018-0346-z
|View full text |Cite|
|
Sign up to set email alerts
|

Contrasting responses of autumn-leaf senescence to daytime and night-time warming

Abstract: Corresponding authors: C Wu (wucy@igsnrr.ac.cn), H Wang (wanghj@igsnrr.ac.cn) 38 and Q Ge (geqs@igsnrr.ac.cn). 39 2 Plant phenology is a sensitive indicator of climate change 1-4 , and plays a significant role in 40 regulating carbon uptake by plants [5][6][7] . Previous studies have focused on spring leaf-out by 41 daytime temperature and the onset of snowmelt time 8-9 , but the drivers controlling leaf 42 senescence date (LSD) in autumn remain largely unknown 10-12 . Using long-term ground 43 phenological re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
128
3
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 188 publications
(143 citation statements)
references
References 49 publications
10
128
3
2
Order By: Relevance
“…is is in accordance with previous studies [16,36]. However, the contribution of mean temperature to LCS variability is low when compared to spring phenology [30], with nonsignificant correlation existing between the mean temperature and LCS variability in most cases, particularly at Mudanjiang, Minqin, and Shenyang. As previous studies suggested, the night temperature has a predominant effect on the leaf coloring date for some deciduous trees [27,37].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…is is in accordance with previous studies [16,36]. However, the contribution of mean temperature to LCS variability is low when compared to spring phenology [30], with nonsignificant correlation existing between the mean temperature and LCS variability in most cases, particularly at Mudanjiang, Minqin, and Shenyang. As previous studies suggested, the night temperature has a predominant effect on the leaf coloring date for some deciduous trees [27,37].…”
Section: Discussionsupporting
confidence: 92%
“…Some studies argued that the effect of temperature difference between day and night on autumn phenology was underestimated, since temperature difference above 15°C was propitious to color presentation of leaves [20,26]. In addition, minimum temperature was also suggested as an influencing factor of autumn phenology that lower autumn minimum temperature would result in earlier leaf coloring date [27][28][29][30]. Although other environmental factors, such as precipitation, photoperiod, and insolation, would also influence autumn phenology through affecting the formation of leaf abscission meristems and plant carboxylation reaction [31], they were more likely to only constrain the temperature-induced changes.…”
Section: Introductionmentioning
confidence: 99%
“…So the same attention should be paid to the interactions between temperature and precipitation. Furthermore, recent studies indicated the preseason maximum daytime and minimum nighttime temperatures produced contrasting effects on the DOD (Yang et al, 2017;Wu et al, 2018). So, in order to improve the accuracy of vegetation phenology modeling, the daytime and nighttime temperatures should be incorporated in autumn phenology models, rather than mean temperature alone in future study.…”
Section: Uncertainties and Limitationsmentioning
confidence: 99%
“…However, it can be anticipated that, sooner or later, agricultural management and/or choice of cultivars will also be adapted to the new potential growing seasons. The drivers of autumn phenology, such as leaf colouring and leaf fall, are still far from being completely understood (Estrella & Menzel, ; Gallinat, Primack, & Wagner, ; Gill et al, ; Wu et al, ).…”
Section: Introductionmentioning
confidence: 99%